Application of Computer Support for Design of Shaft Furnaces – Cupolas - Dajczer, Grzegorz; Dańko, Rafał (Journal of Casting & Materials Engineering, 2018)
Designing a machine’s constructions and an object’s structures is one of the areas of technology design. The complexity of the structure is defined by the technology for which it is used. Following the theory of construction and mechanisms, the full characteristics of a machine or device is defined by its shape and operating parameters. The shape reflects geometry. As a result of using the correct parameters, the construction should functional correctly (which means according to its general principles of operation). The project of any structure is a creative process performed by a team of designers and constructors. The contemporary design is not solely based on the personal preferences of engineers. More and more scientific and computerized design methods are being introduced to this process. They are characterized as computer-aided systems and are based on algorithms, programs, and IT equipment. This article presents the methodological application of computer-aided design on an example of the design of shaft furnaces that are used in foundries as cast iron smelters. These furnaces, called cupolas, have again become objects of interest for research. In the design of the cupola construction, Autodesk Inventor techniques were used.